Experimental Research and Sensitivity Analysis of Mudstone Similar Materials Based on Orthogonal Design - Caoxuan Wen; Shanpo Jia; Xiaofei Fu; Lingdong Meng; Zhenyun Zhao (Advances in Materials Science and Engineering)
Due to the strong hydration sensitivity of mudstone, drilling of deep mudstone is difficult and pricy, which results in the study on its physical and mechanical properties inseparable from similar material tests. On these bases, triaxial compression and Brazilian tensile tests of the original mudstone drilled from the caprock of the D5 aquifer structure are carried out. Then, orthogonal experiments of mudstone similar materials with river sand and barite powder as aggregate and cement and gypsum as the binder are conducted, which include 3 factors that, respectively, are mass ratio of aggregate to binder, mass ratio of cement to gypsum, and barite powder content, and each factor contains 5 levels, totalling 25 groups of 150 samples. By comparing the results of mudstone and artificial samples made of similar materials, it is obvious that artificial samples and mudstone are significantly similar in terms of density, compressive strength, elastic modulus, and compressive strength when the aggregate-binder ratio is about 4, 8, 5, and 4, respectively. Further sensitivity analysis showed that the aggregate-binder ratio played a major role in controlling the properties of artificial samples, while the sensitivity of different parameters to the cement-gypsum ratio and barite content was different. The results indicate that the selected raw materials and their proportion are feasible, which can meet similar requirements and can be a reference for similar material experimental research of target mudstone.